Archives judiciaires et archives de la folie. Ou comment un repris de justice, en s’enfuyant de l’asile où il était enfermé, remit en question tout un système (Cagliari - Italie, 1854) - Cecilia Tasca; Mariangela Rapetti (Criminocorpus)
The essay analyses the events relating to the construction of the psychiatric unit of the new city public hospital of Cagliari, in Sardinia, through the cross-examination of sources. The application of Savoy laws in Sardinia appears to be ephemeral for what concerns mental health. If, on the one hand, the law makes it compulsory for criminals to undergo a psychiatric assessment as well as for furious maniacs to be admitted to hospital, the care centers available in the island are, on the other hand, in such a state that the persons hospitalized for psychiatric illnesses run the risk of seeing their condition worsen rather than improve, leaving aside the fact that admission is often denied to them tout court. In 1854, when a patient, already well-known to the Public Prosecutor’s Office and to the courthouse, escapes twice from the care center, the Home Office and public opinion became aware for the first time of the conditions in which psychiatric patients live in Sardinia. The result of such new consciousness is a process of reforms aimed at modifying the project for the new hospital, which dates back to 1844, and the institution of a special unit destined to become a psychiatric ward and which will be inaugurated as late as in 1859.